Zakat and Taxes in Islamic Overview: in terms of Benefit - Darvina Darvina; Safrudin Halimy Kamaluddin; Muhammad Ridho Nur (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2020)
This article will discuss Zakat and taxes from an advantageous perspective. Zakat and taxes are two obligations that must be carried out by Muslims in Indonesia. This tax is charged to every citizen who should pay taxes, which are at first glance looks very contradicted to Islamic teachings. In Islamic teachings, groups of people are obliged to spend a small portion of their assets as Zakat, namely those who have been categorized as capable persons already having had Nishab to give Zakat. By conducting literature studies and a descriptive analysis approach, it is found that Zakat contains the hope of obtaining blessings, cleansing the soul, cultivating it with various virtues, and fostering cleanliness and benefits on the assets owned. Tax and Zakat possess the same purpose namely a source of funds to create a just and prosperous society by sustaining equitability between material and spiritual needs. Taxes are used to finance activities in the fields and sectors of development. The distribution of Zakat to Mustahik, especially the poor and needy people, is expected to support their economic life to help national economic growth.